An AIE luminogen-based electropolymerized film: an ultrasensitive fluorescent probe for TNP and Fe3+ in water. (29th October 2020) - Hao, Hongmin; Xu, Chao; Luo, Haiyuan; Yang, Jinglian; Liu, Cong; Xu, Bingjia; Shi, Guang; Xing, Xiaobo; Chi, Zhenguo
Abstract : A fluorescent POP film (polyPhTPECz) which acted as an excellent multifunctional and reusable fluorescent probe was prepared by using an electropolymerization (EP) method. Abstract : Porous organic polymers (POP) are potential materials for fluorescent sensors because of their extended π-conjugated framework and porous structure. However, poor processability and photofunctionality are the major limitations for their practical applications. Here, a highly emissive photofunctional POP film (polyPhTPECz) was constructed using a simple in situ electropolymerization (EP) method. A novel high-luminescence aggregation-induced emission (AIE) molecule (PhTPECz), composed of multiple AIE groups as the central "core" and eight carbazole electroactive "arms, " was used as an electroactive precursor. Two possible twist conformations of polyPhTPECz were speculated and the corresponding pore diameters calculated to be ∼1.2 and 2.9 nm, respectively. These polyPhTPECz EP films were excellent multifunctional and reusable luminescent sensors for 2, 4, 6-trinitrophenol (TNP) and Fe 3+ in an aqueous medium. The obtained limit of detection (LOD) was 3.8 and 10.0 nM for sensing TNP and Fe 3+, respectively. These films also showed sensitive detection for TNP vapor. The fluorescence-quenching mechanism for TNP was a combination of electron transfer and resonance energy transfer. These excellent properties were mainly attributed to the high fluorescence property and cross-linked porous texture of these polyPhTPECz films.